2021
DOI: 10.1002/aoc.6535
|View full text |Cite
|
Sign up to set email alerts
|

Novel metal complexes with pyrano[3,2‐c]quinoline‐3‐carboxaldehyde: Synthesis, spectroscopic, molecular modeling, QSAR, antimicrobial, and antitumor studies

Abstract: Reaction of 6‐ethyl‐4‐hydroxy‐2,5‐dioxo‐5,6‐dihydro‐2H‐pyrano[3,2‐c]quinoline‐3‐carboxaldehyde (HL) with some metal ions, namely, manganese (II), cobalt (II), nickel (II), zinc (II), cadmium (II), chromium (III), iron (III), cerium (III), oxovanadium (IV), and dioxouranium (VI), yielded a new series of metal complexes; with the general formula, [MHnLAm(H2O)x]Xy·zH2O, n = 0–1, A = NO3− or OAc−, m = 0–2, X = NO3− or SO42−, y = 0–1, and z = 0–3. The metal complexes were characterized by elemental analysis, molar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The 1 H NMR spectrum of 6‐ethyl‐4‐hydroxy‐2,5‐dioxo‐5,6‐dihydro‐2 H ‐pyrano[3,2‐ c ]quinoline‐3‐carboxaldehyde was previously reported in our earlier research. [ 25 ] The 1 H NMR spectrum of the prepared ligand ( H 2 L ) (Figure 2, Table 3) showed the disappearance of the aldehydic proton, which was observed at δ 10.03 ppm in the 1 H NMR spectrum of the carboxaldehyde. A new signal attributed to the azomethine (CHN) proton appeared at δ 8.22 ppm; also, the spectrum showed D 2 O exchangeable signals assignable to NH 2 , NH, and OH at δ 6.73, 9.41, and 12.39 ppm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 1 H NMR spectrum of 6‐ethyl‐4‐hydroxy‐2,5‐dioxo‐5,6‐dihydro‐2 H ‐pyrano[3,2‐ c ]quinoline‐3‐carboxaldehyde was previously reported in our earlier research. [ 25 ] The 1 H NMR spectrum of the prepared ligand ( H 2 L ) (Figure 2, Table 3) showed the disappearance of the aldehydic proton, which was observed at δ 10.03 ppm in the 1 H NMR spectrum of the carboxaldehyde. A new signal attributed to the azomethine (CHN) proton appeared at δ 8.22 ppm; also, the spectrum showed D 2 O exchangeable signals assignable to NH 2 , NH, and OH at δ 6.73, 9.41, and 12.39 ppm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Pyrano[3,2‐ c ]quinoline‐3‐carboxaldehyde derivative (2.85 g, 0.01 mol) that was synthesized according to a method described elsewhere [ 25 ] was dissolved in hot absolute ethanol (40 ml); after that, semicarbazide hydrochloride (1.12 g, 0.01 mol) dissolved in water (5 ml) was added. Then, the reaction mixture was heated under reflux for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Hansch and Leo, highly lipophilic compounds will participate in the lipid interior of membranes and be retained there. A drug has low solubility with a higher log P and has difficulty penetrating lipid membranes with a lower log P. 48 Lipophilicity (log P) is a feature that affects absorption, solubility, distribution, excretion qualities, metabolism, and pharmacological activity; normalized B.S. and normalized C.A.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…These compounds are also widely utilized in medicine, where they have shown effective as anticancer agents, antibacterial agents, antiseptics, and antineoplastics. 29 A literature survey indicated that complexes of Co(II), Ni(II), and Cu(II) with single azo or 8-hydroxyquinoline (HQ) ligand were reported to show anticancer, 30,31 antitumor, 32,33 antioxidant, 34,35 and antimicrobial activity. 36,37 Also, previous studies indicated that Co(II), Ni(II), and Cu(II) complexes based on azo-8-hydroxyquinoline derivatives exhibited good to moderate affinity to dyeing polyester fabrics 38 and promising antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%